2010
DOI: 10.1128/aem.00527-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Limulus Amebocyte Lysate and Recombinant Factor C Assays for Assessment of Airborne Endotoxin

Abstract: As a potent inflammatory agent, endotoxin is a key analyte of interest for studies of lung ailments in domestic environments and occupational settings with organic dust. A relatively unexplored advance in endotoxin exposure assessment is the use of recombinant factor C (rFC) from the Limulus pathway in a fluorometric assay. In this study, we compared airborne endotoxin concentrations in laboratory-and field-collected parallel air samples using the kinetic Limulus amebocyte lysate (LAL) assay and the rFC assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…In other studies performed in large U.S. inner cities (15,16) and in a European consortium study (2), investigators reported higher endotoxin levels in bedroom floor and/or bedding (Table 5). Although endotoxin measurements in several national and regional studies were done by our laboratory, caution must be exercised when comparing endotoxin data across laboratories, owing to differences in sample collection, storage, extraction, and assay techniques (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies performed in large U.S. inner cities (15,16) and in a European consortium study (2), investigators reported higher endotoxin levels in bedroom floor and/or bedding (Table 5). Although endotoxin measurements in several national and regional studies were done by our laboratory, caution must be exercised when comparing endotoxin data across laboratories, owing to differences in sample collection, storage, extraction, and assay techniques (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…PFW with Tween 20 and normal saline (NS) were frequently recommended as extraction solutions (Oppliger et al, 2005;Madsen et al, 2006;Dutil et al, 2009;Thorne et al, 2010). In this study, endotoxin concentrations were detected and evaluated under different types and different concentration gradient solution conditions.…”
Section: Optimization Methodsmentioning
confidence: 99%
“…A 1-mL aliquot was removed and assayed for endotoxin content using the kinetic chromogenic Limulus amebocyte lysate (LAL) assay (Lonza) as described. 10 Briefly, 100 μL of the aliquot was diluted in an 8-step series of 1:10 dilutions using EF water (Lonza) in borosilicate tubes that had been depyrogenated by heating overnight at 160°C. A 12-point calibration curve was generated (r 2 = 0.999) ranging from 0.0244 to 50 EU/mL of Escherichia coli 0111:B4 control standard endotoxin calculated from the maximum slope of the absorbance vs time plot for each well.…”
Section: Lpsmentioning
confidence: 99%